Growth process in business and social entrepreneurship: the case of Brazil - Vanni, Giulio (2015)
The purpose of the dissertation is to investigate in depth the difference between the challenges social and business entrepreneurs face in the growth phase of their business in the particular environment of Brazil. This objective has been achieved through a two-steps methodology. The first step is a set of in-depth interviews carried out with industry experts such as professors, venture capitalists, consultants, fund managers or people involved in the support of growing startups (i.e. accelerators). These interviews allowed, first, to build a general perspective on the environment entrepreneurs operate into and to identify a list of challenges entrepreneurs face in the growth process of their business. This list was completed with the additional challenges identified in the previous literature. The second step of the methodology was to test the relevance of these challenges in the mind and experience of social and traditional entrepreneurs. A questionnaire was then submitted to 145 social and 286 traditional entrepreneurs. The results were statistically analyzed to test the relative relevance of these challenges for one group of entrepreneurs with respect to the other. The outcome of the analysis was significant. The most relevant challenges identified were, for both groups, taxation, bureaucracy, finding the right employees, creating effective teams, measuring firm performance and social value creation and obtaining funds. On the other side motivation, innovation, competition and lack of market space for growth represented the least relevant issues in the minds of entrepreneurs. This rank however did not differ significantly from social to traditional entrepreneurs. This testifies that in Brazil social and traditional entrepreneurs face the same set of challenges despite the widespread belief of the opposite.